Theory and method in higher education research - Huisman, Jeroen; Tight, Malcolm (Bingley, U.K. : Emerald Publishing Limited, 2018)
Higher education research is a developing field internationally, which is attracting more and more researchers from a greatvariety of disciplinary backgrounds within and beyond higher education institutions. As such, it is an arena within which a wide range of theories,methods and methodologies are being applied. This volume of Theory and Method in Higher Education Research contains analyses and discussions of, amongst others, topic modelling, geometric data analysis,creativity and playfulness, longitudinal network analysis, grounded theorymethods and autonetnography.
Prelims -- Using the sociology of Basil Bernstein in higher education research -- A probabilistic approach to studies in higher education -- Refocusing threshold concepts: surfacing and attending to student misconceptions as a necessary (and safer) form of liminal learning -- Creativity and playfulness in higher education research -- Capturing hybrid institutional logics in higher education: qualitative document analysis as methodological approach -- Globalisation and differentiation in higher education systems -- Exploring the complex social spaces of higher education: on the uses and challenges of geometric data analysis and topological approaches -- Methodological tracks to study research collaboration networks in higher education -- Longitudinal peer network data in higher education -- Casting the 'net' in autonetnography: exploring the potential for analytic autonetnography as an emerging e-research methodology -- Practice-focused, constructivist grounded theory methodology in higher education leadership research -- Human and social capital and their application in higher education research -- The state of the art of higher education research on Flanders -- Index.
Includes index.
Print version record
Keywords: Education, Higher -- Research; Education -- Higher; Higher & further education, tertiary education